Justification for Chest Physiotherapy during Ultra‐Protective Lung Ventilation and Extra‐Corporeal Membrane Oxygenation: A Case Study. (17th August 2013) - Cork, G.; Barrett, N.; Ntoumenopoulos, G.
Abstract Background and purpose This case report describes the chest physiotherapy (CPT) intervention provided to a 32‐year old man with severe respiratory failure undergoing extra‐corporeal membrane oxygenation (ECMO) support and ultra‐protective ventilatory strategy. Low tidal volume ventilation when used in patients with extremely low dynamic respiratory compliance may predispose the patient to secretion retention, and the role of CPT in this setting is unclear. Method The method used is a single subject case report. Written consent obtained from patient's representative. Summary Secretion clearance in this patient was initially limited to suctioning; however, after developing major airway occlusion secondary to impacted secretions, he received intensive CPT consisting of positioning, ventilator hyperinflation, expiratory chest wall shaking and suctioning. After 13 days of two to three times daily CPT, the patient weaned from ECMO support. Discussion Regular CPT may have facilitated secretion clearance and lung recovery in this patient. Future research should investigate the optimal CPT techniques for patients with sub‐dead space tidal ventilation and extremely low dynamic respiratory compliance during ECMO with ultra‐protective ventilatory strategy (UPVS). Copyright © 2013 John Wiley & Sons, Ltd.